ANALYSIS OF THE FLIGHT SAFETY MANAGEMENT SYSTEM IN THE PRACTICE OF INTERNATIONAL AIRPORTS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The state of the aviation transport system at international airports, in which therisks associated with aviation activities related to the operation of aircraft or directly providingsuch operation are reduced and maintained at an acceptable level. The safety management system,which covers the organizational structure, responsibilities, procedures, processes and provisionsdesigned to implement the policy in the field of flight safety in air traffic services, provides thedesired or acceptable level of safety and provides for the implementation of safety control.
Keywords: Flight safety, aviation accidents, achieved safety, risk analysis, airport, danger, errors, aircraft, airfield, air traffic.